2011
DOI: 10.1039/c1cy00127b
|View full text |Cite
|
Sign up to set email alerts
|

Model Ag/HOPG catalysts: preparation and STM/XPS study

Abstract: Model catalysts-Ag on highly oriented pyrolytic graphite (Ag/HOPG)-have been studied using scanning tunneling microscopy (STM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and X-ray induced Auger electron spectroscopy (XAES). Two types of catalysts were compared: Ag nanoparticles supported on sputtered and non-sputtered HOPG, and the influence of graphite surface defects on the stabilization of Ag nano-sized particles was discussed. A procedure for the preparation of stable (up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 36 publications
(66 reference statements)
4
30
0
Order By: Relevance
“…The asymmetry in Fig. 3c is explained by an increased ratio between the two peaks at 531.8 and 530.5 eV, which are commonly attributed to carboxyls and the electrophyllic oxygen state on Ag, respectively 39 . The strong increase in the peak at 531.8 eV in regions ii-v is attributed to the large portion of graphene edge states that interact with the oxidized/tarnished Ag surface after the sample is exposed to atmosphere.…”
Section: Graphene Growth Morphologymentioning
confidence: 99%
“…The asymmetry in Fig. 3c is explained by an increased ratio between the two peaks at 531.8 and 530.5 eV, which are commonly attributed to carboxyls and the electrophyllic oxygen state on Ag, respectively 39 . The strong increase in the peak at 531.8 eV in regions ii-v is attributed to the large portion of graphene edge states that interact with the oxidized/tarnished Ag surface after the sample is exposed to atmosphere.…”
Section: Graphene Growth Morphologymentioning
confidence: 99%
“…X‐ray photoelectron spectroscopy (XPS) of both the printed AgNW and the vacuum‐deposited Ag film showed binding energies of Ag 3d 5/2 at 368.2 eV and Ag 3d 3/2 at 374.2 eV, which correspond to pure metallic Ag (Figure S9a,b, Supporting Information) . However, in the O 1s spectrum, AgNW had three clear peaks at binding energies of 529.7, 531.4, and 532.9 eV, which are originated from the O in CuO, in Cu(OH) 2 , and in a small amount of adsorbed H 2 O molecules on the surface of AgNW, respectively, whereas the Ag film had a small peak at 530.4 eV that is attributed to O adsorbed to the electrophilic state of Ag (Figure S9c, Supporting Information) . The Cu 2p spectra of AgNW also clearly showed the existence of CuO in AgNW with the Cu 2p 3/2 (933.7 eV) and Cu 2p 1/2 (953.5 eV) peaks from CuO, and two CuO/Cu(OH) 2 satellite peaks (Figure S9d, Supporting Information) .…”
mentioning
confidence: 99%
“…Annealing at 500 C in UHV was found to restore the HOPG surface. In air, studies have shown that annealing in oxygen is found to burn the surface beginning at 500 C. 39,57,58,66,78 In this study, etching was found to occur at these temperatures, as discussed next.…”
Section: Resultsmentioning
confidence: 51%